Monozygotic twins diagnosed simultaneously with RAM immunophenotype acute myeloid leukemia. (15th September 2018) - Abu‐Arja, Rolla F.; Dargart, Jamie L.; Bajwa, Rajinder P. S.; Kahwash, Samir B.; Auletta, Jeffery J.; Rangarajan, Hemalatha G.
Abstract: AML with the RAM immunophenotype is associated with extremely poor prognosis. We report a rare case of monozygotic twins presenting simultaneously at the age of 2 years with RAM AML. Each twin underwent a myeloablative 7/10 unrelated umbilical cord blood transplant. Pretransplant Twin A's bone marrow was negative for MRD by flow cytometry (<0.01%) unlike Twin B's bone marrow (0.07%). Twin A is alive in remission 3 years from transplant. Twin B developed primary graft failure, but subsequently rescued with a haploidentical stem cell transplant. However, she relapsed and died 13 months from diagnosis. The twins' clinical courses demonstrate that upfront intensive chemotherapy to achieve negative MRD, followed by allogeneic hematopoietic stem cell transplant as postremission intensification strategy, should be considered in this high‐risk AML.